Perubahan Iklim Kala Miosen Akhir Berdasarkan Analisis Palinologi Di Formasi Lemau, Bengkulu - Mentari, Sakilla; Wijaya, Muhammad Eval Juni; Adesti Audina Ulfah (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
Fossil pollen and spores can be used to determine the age and depositional environment of sedimentary rocks, as well as to reconstruct the paleoclimate at the time the rocks were formed. The use of pollen and spores for paleoclimate reconstruction in Sumatra remains limited. This study aims to identify the pollen and spore assemblages of the Lemau Formation and to reconstruct Late Miocene climatic changes based on these assemblages. Sampling was conducted through a measured stratigraphic section at 5–8 cm intervals, and laboratory analysis employed the hydrogen peroxide method. A total of ten rock samples were collected and analyzed. The results indicate that the study area experienced a warm climate with five episodes of humidity variation, interpreted from changes in the abundance of arboreal pollen, non-arboreal pollen, Graminae, spores, and montane pollen. The warm climatic conditions and humidity fluctuations are inferred to be related to the global Middle Miocene Climate Optimum (MMCO) event, as well as to uplift activity of the Bukit Barisan Range in the study area.